MODEL DEVELOPMENT OF OPEN SOURCE ERP SYSTEM ADOPTION AMONG SMEs BY CONSIDERING TECHNOLOGY, HUMAN AND ENVIRONMENT CONTEXT - ANDRIZA NIM : 23416067, YUKA
Nowadays ERP systems are widely used by companies all over the world. But the use of ERP systems requires a lot of cost, starting from the initial process until the maintenance process so this system is rarely used by Small Medium Enterprises (SMEs). Another thing is caused by not all the functions that are in the ERP systems used in the business of Small Medium Enterprises itself, only a small part of the function from the systems that will be used. Therefore, Open Source ERP system becomes the solution for business process of SMEs, where this system is very suitable for companies that aren’t complex and have limited resources. This study aims to determine the factors that significantly affect the adoption of Open Source ERP system among SMEs. These factors are grouped into three contexts, namely technology, people and environment. Based on the previous researches the hypothesized factors affecting adoption of Open Source ERP system are relative advantage, compatibility, complexity, decision maker’s innovativeness, decision maker’s IT/IS knowledge, IT/IS expertise, competitive pressure and government support. The object of the study is SMEs, which have not use the Open Source ERP system. The data collection instrument used is a questionnaire with the likert scale of 6 points. A total of 81 data collected from SMEs located in Bandung and surrounding areas. Partial Least Square method (PLS-SEM) is used to process the data that have been collected. This method was used because it was suitable for low samples size and non-normality data. The results of the data processing showed that the adoption of an Open Source ERP system is affected by relative advantage, decision maker’s innovativeness, IT/IS expertise and competitive pressure. This finding indicate that the technology, people and environment contexts affects the adoption of Open Source ERP system among SMEs.